1997
DOI: 10.1038/bjc.1997.151
|View full text |Cite
|
Sign up to set email alerts
|

An anti-cancer derivative of butyric acid (pivalyloxmethyl buterate) and daunorubicin cooperatively prolong survival of mice inoculated with monocytic leukaemia cells

Abstract: Summary A derivative of butyric acid, pivalyloxymethyl butyrate , inhibited the proliferation and induced apoptosis of mouse monocytic leukaemia Mm-A cells, although sodium butyrate, but not AN-9, induced differentiation of the cells. AN-9 and DNA-specific antineoplastic agents synergistically inhibited the growth of Mm-A cells, and the simultaneous treatment was required to evoke the maximum growth-inhibitory effect. On the other hand, there was no synergy between butyrate and the drugs, or AN-9 and anti-meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 17 publications
(22 reference statements)
1
41
0
Order By: Relevance
“…Pivaloyloxymethyl butyrate (AN-9) releases formaldehyde as well as butyric acid and has been used as a histone deacetylase inhibitor (21 -23). The combination of daunorubicin with pivaloyloxymethyl butyrate is synergistic in various cell lines and mouse models of leukemia (24,25). Although initially thought to be due to an interaction of the butyric acid with the anthracycline, the synergistic interaction with doxorubicin has been subsequently found to be primarily due to formaldehyde release, which results in efficient DNA adduct formation (26).…”
Section: Introductionmentioning
confidence: 99%
“…Pivaloyloxymethyl butyrate (AN-9) releases formaldehyde as well as butyric acid and has been used as a histone deacetylase inhibitor (21 -23). The combination of daunorubicin with pivaloyloxymethyl butyrate is synergistic in various cell lines and mouse models of leukemia (24,25). Although initially thought to be due to an interaction of the butyric acid with the anthracycline, the synergistic interaction with doxorubicin has been subsequently found to be primarily due to formaldehyde release, which results in efficient DNA adduct formation (26).…”
Section: Introductionmentioning
confidence: 99%
“…Formaldehyde reacts with doxorubicin and induces doxorubicin-DNA adduct formation and a synergistic cytotoxic response in tumor cells in culture (20,23). A combination of daunomycin (an anthracycline that is structurally similar to doxorubicin) and AN-9 was shown to increase the survival of mice inoculated with mouse monocytic leukemic cells (24). AN-9 was initially synthesized as a butyric acidreleasing prodrug to function as a histone deacetylase inhibitor (25).…”
Section: Introductionmentioning
confidence: 99%
“…18 Earlier studies in mouse tumor models have demonstrated that AN-9 is an effective antitumor agent and displays low toxicity. 19 Currently, AN-9 is being studied in a phase II clinical trial for non-small cell lung cancer. To date, all in vitro and in vivo studies of AN-9 have been confined to solid tumors, with the exception of a murine monocytic leukemia and the HL60 cell line.…”
Section: Introductionmentioning
confidence: 99%